2017
DOI: 10.3171/2017.1.peds16496
|View full text |Cite
|
Sign up to set email alerts
|

Shunting outcomes in posthemorrhagic hydrocephalus: results of a Hydrocephalus Clinical Research Network prospective cohort study

Abstract: OBJECTIVEPrevious Hydrocephalus Clinical Research Network (HCRN) retrospective studies have shown a 15% difference in rates of conversion to permanent shunts with the use of ventriculosubgaleal shunts (VSGSs) versus ventricular reservoirs (VRs) as temporization procedures in the treatment of hydrocephalus due to high-grade intraventricular hemorrhage (IVH) of prematurity. Further research in the same study line revealed a strong influence of center-specific decision-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
92
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 110 publications
(100 citation statements)
references
References 34 publications
(64 reference statements)
4
92
0
4
Order By: Relevance
“…Once again, there was no significant difference between the number of infants VP shunted between the two groups (38% and 39%). A recent prospective cohort study from the Hydrocephalus Clinical Research Network reported that 56% of those treated when the frontal-occipital horn ratio exceeded 0.55 with clinical symptoms were VP shunted 19. In a recent observational cohort study, as many as 92% of preterm infants required a shunt when treatment was started following onset of clinical symptoms 20…”
Section: Discussionmentioning
confidence: 99%
“…Once again, there was no significant difference between the number of infants VP shunted between the two groups (38% and 39%). A recent prospective cohort study from the Hydrocephalus Clinical Research Network reported that 56% of those treated when the frontal-occipital horn ratio exceeded 0.55 with clinical symptoms were VP shunted 19. In a recent observational cohort study, as many as 92% of preterm infants required a shunt when treatment was started following onset of clinical symptoms 20…”
Section: Discussionmentioning
confidence: 99%
“…5 Given the high rates of infection, dysfunction and life-long dependence after VP-shunt insertion, it would be beneficial if a treatment could reduce the risk of shunt requirement. 6,7 Removing the hemorrhagic CSF by lumbar punctures or taps from a ventricular reservoir may reduce the need for VP-shunt placement, since removal of CSF that contains blood components, protein, and cytokines might re-establish normal CSF circulation. 8 Although, optimum timing of intervention continues to be a matter of debate in the neonatal literature, there is accumulating evidence showing the beneficial effects of early intervention on ventricular dilatation and outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies on IVH outcomes have relied on single-institution data, collaborative networks, or patient registries, but there is a dearth of longitudinal, population-level data regarding IVH [8, 17, 23, 25, 34, 43]. Few studies have investigated the long-term neurosurgical outcomes of infants affected with IVH, such as shunt complications [2, 9, 10, 21, 29, 30, 39, 40].…”
Section: Introductionmentioning
confidence: 99%